Lithium suppresses Aβ pathology by inhibiting translation in an adult Drosophila model of Alzheimer’s disease. - Sofola-Adesakin, Oyinkan; Castillo-Quan, Jorge Ivan; Rallis, Charalampos; Tain, Luke S.; Bjedov, Ivana; Rogers, Iain; Li, Li; Martinez, Pedro; Khericha, Mobina; Cabecinha, Melissa; Bahler, Jurg; Partridge, Linda (Frontiers in Aging Neuroscience, 2014)
The greatest risk factor for Alzheimer’s disease (AD) is age, and changes in the ageing nervous system are likely contributors to AD pathology. Amyloid beta (Aβ) accumulation, which occurs as a result of the amyloidogenic processing of amyloid precursor protein (APP), is thought to initiate the pathogenesis of AD, eventually leading to neuronal cell death. Previously, we developed an adult-onset Drosophila model of AD. Mutant Aβ42 accumulation led to increased mortality and neuronal dysfunction in the adult flies. Furthermore, we showed that lithium reduced Aβ42 protein, but not mRNA, and was able to rescue Aβ42-induced toxicity. In the current study, we investigated the mechanism/s by which lithium modulates Aβ42 protein levels and Aβ42 induced toxicity in the fly model. We found that lithium caused a reduction in protein synthesis in Drosophila and hence the level of Aβ42. At both the low and high doses tested, lithium rescued the locomotory defects induced by Aβ42, but it rescued lifespan only at lower doses, suggesting that long-term, high-dose lithium treatment may have induced toxicity. Lithium also down-regulated translation in the fission yeast Schizosaccharomyces pombe associated with increased chronological lifespan. Our data highlight a role for lithium and reduced protein synthesis as potential therapeutic targets for AD pathogenesis.